INTEGRASI ARTIFICIAL INTELLIGENCE DALAM DESAIN PEMBELAJARAN AKIDAH AKHLAK UNTUK MENINGKATKAN PERSONALISASI BELAJAR DAN AKHLAK DIGITAL DI MTSN 2 PONTIANAK - ’Abidah, Nur; Wahab, Wahab (Universitas Tanjungpura, 2026)
The development of Artificial Intelligence (AI) in education provides new opportunities for adaptive and personalized learning. This study aims to design and test an AI-based Islamic Religious Education (Akidah Akhlak) learning model that enhances personalized learning and digital ethics formation among eighth-grade students at Madrasah Tsanawiyah Negeri 2 Pontianak. The research applies a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The participants consist of 32 purposively selected students. The results reveal that AI-based Akidah Akhlak learning design increases personalized learning by 35% and strengthens key digital ethics indicators such as honesty, responsibility, and self-control. The integration of AI reinforces the teacher’s role as an ethical overseer to ensure moral and Islamic value alignment in technology use.